INCREASING THE VISITS AND RETAINING E-LOYALTY TOWARDS WEBSITE - Candra Diana, Elsa; Mulia, Dipa (Dinasti International Journal of Management Science, 2020)
The growth of users and transactions through e-commerce create its own phenomenon of fluctuating visits on website. Its was valuation regarding how often the website being visited or attracts that attention from visitors. This could be measured by examining those influences from customer interface quality, customer satisfaction and switching cost towards E- loyalty on the use of e-commerce website. Research data obtained through a questionnaire that distributed to 150 respondents by Structural Equation Modeling test method of IBM SPSS AMOS 22. All Results show that Customer Interface Quality has capable to provide positive and significant impact towards e-loyalty, as well as Customer Satisfaction which partially or as a mediate variable for Quality Customer Interface that also signs positive and significant influence over it. From these result tells that Switching Cost does not had significant influence or either partially as a mediator to e-loyalty. Customer Satisfaction is most influential variable to e-loyalty on website visits.